Integrating Sustainable Development Goal 4 (SDG 4) and Education in India :: Assessment and Action Plan - Kumar, Mallika (JOURNAL OF INDIAN EDUCATION, 2023)
Out of the total 17 SDGs of United Nations, SDG 4 specifically deals with quality education that talks about ensuring inclusive and equitable quality education, and promote lifelong learning opportunities for all. Out of different targets set for quality education, Target 4.3 states, “Ensure access to girls, boys, women and men quality and affordable education, including university”. The paper deals more on Target 4.3 of SDG on quality education. The paper shares insights about SDG 4 (Quality Education) and how can academia, along with the students contribute in shaping the future. In this paper, an attempt has been made to link the efforts being made at various levels, i.e., the Government, universities and colleges to fulfill the targets of the education set by United Nations. While the first part of the paper talks more about SDG 4 and its understanding, the second part deals with the initiatives taken up by the universities and the government towards contributing to the SDG 4 goals and the third part talks about the strategy for the future. The purpose of the paper is to develop awareness and undertanding on SDG 4, inform about the role of education, teachers and educational institutions in supporting the nation to attain SDG 4 targets. The paper also assesses the current status of India with regard to SDG 4, and alignment of the initiatives and policies of education with that goal. The paper concludes with the challenges, and the need for action at individual, institutional and community level for the realisation of SDG 4.